Understanding The Phenomenon of Fake Crazy Rich and Fraudulent Investment in Indonesia from the Philosophy of Happiness in Hazrat Inayat Khan’s Sufism - Roswantoro, Alim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The phenomenon of the “crazy rich” as a representation of modern materialism and hedonism has influenced the lives of the young generation of Indonesia in the millennial era. The glamorous and luxurious lifestyle displayed by the “crazy rich” has attracted many individuals to show off their wealth, even when the wealth is not yet truly owned. This phenomenon often ends in investment fraud harming many parties. This study aims to analyze the phenomenon of the “fake crazy rich” and fraudulent investment in Indonesia from the perspective of Inayat Khan's philosophy of happiness in Sufism, distinguishing between true happiness and false happiness. This study uses a qualitative approach with Inayat Khan's theoretical analysis as a conceptual framework. Data were collected through literature studies and analysis of relevant social phenomena. The study found that the phenomenon of the “fake crazy rich” and investment fraud in Indonesia reflects the efforts of the younger generation to pursue material wealth as a measure of life success. However, from Inayat Khan's perspective, this is a form of false happiness not providing true life satisfaction, but suffering and humiliation. This study provides a theoretical contribution by applying Inayat Khan's philosophy of happiness to understand contemporary social phenomena in Indonesia. In addition, this study also provides critical insights into the impact of materialism and hedonism on the younger generation and the importance of distinguishing between true happiness and false happiness in modern life.